PERLINDUNGAN PEKERJA MIGRAN INDONESIA DITINJAU DARI ASAS KESETARAAN DAN KEADILAN GENDER - Dina Fauzhar Rahman (Indonesian State Law Review, 2021)
Protection stipulated in Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers is all efforts to protect the interests of prospective Indonesian Migrant Workers and / or Indonesian Migrant Workers in order to ensure the fulfillment of their rights in all activities before work, during and after work. The method used is descriptive qualitative with a normative juridical approach. The results show that the protection of Indonesian Migrant Workers in terms of the principles of gender equality and justice can be seen in indicators of gender equality and justice, namely; 1). access, 2). participation, 3). Control and 4). We can find benefits in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers which are scattered in the provisions of this Law, namely: 1). Protection in Pre-Placement, 2). Protection at the time of placement, and 3). Protection after placement, as well as legal, social and economic protection. So it can be concluded that this law is responsive to gender equality and justice. Efforts to protect Indonesian Migrant Workers are viewed from the principles of gender equality and justice. Namely by way of the Regulatory Structuring Efforts carried out by the government to improve Law No. 39 of 2004 concerning the Placement and Protection of Indonesian Workers Abroad with the new Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers based on equality indicators. and gender justice, namely; 1). access, 2). participation, 3). control and 4). benefits, which are oriented towards the protection of Indonesian Migrant Workers without discrimination.